Pancreatic Cyst Aspirate CEA Levels: Two’s the Charm - Nasr, John Y; McGrath, Kevin (JOP. Journal of the Pancreas, 2011)
Context Pancreatic cysts are increasingly detected incidentally, many of which are premalignant. Despite EUS-FNA and CEA level measurement, the diagnosis of a premalignant cyst may remain uncertain. Case report We report two cases of incidentally found pancreatic cysts where initial EUS-FNA cyst aspirates yielded thin fluid with very low CEA levels. Repeat aspirations one year later revealed markedly different results (slightly viscous fluid with significantly elevated CEA levels) which prompted surgical resection in both cases. Final surgical pathology revealed mucinous cystic neoplasms. Conclusion Pancreatic cyst fluid CEA levels may increase over time, possibly due to neoplastic progression. A heightened index of suspicion for a neoplastic cyst should remain in the appropriate patient population, despite conflicting data. In cases of initial low aspirate CEA levels, we recommend a repeat EUS-FNA at a later date to exclude a premalignant lesion. Image: Resected mucinous cystic neoplasm.